CAPITAL MARKET STUDY GROUP (KSPM) STRATEGY IN ATTRACTING STUDENTS TO INVEST IN SHARIA - Fina, Asro; Aji, Bayu; Inawan, Enita Rizki (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
KSPM contributes to improving its human resources by providing guidance and training on the capital market and investment. The delivery method by KSPM relates to the introduction of sharia principles and the application or practice of investing in the capital market. This study aims to identify the strategies developed by KSPM IAIN Kudus to attract students to invest, the work ethic of KSPM IAIN Kudus both when carrying out duties at the Sharia Investment Gallery of IAIN Kudus and socializing the capital market in attracting students to invest in sharia. This research is a qualitative research, data collection is obtained from primary data and secondary data through the methods of observation, interviews, and documentation. The results of the study show that the KSPM work ethic that has been appropriate and well implemented is respecting time, honesty, commitment, strong stance, discipline, consequence, and responsibility. In addition, KSPM's efforts to attract students to invest are by organizing various activities such as capital market schools and ngobrol seputar investasi (NGOPI). Keywords: Sharia Investment, Interest and Strategy